2018
DOI: 10.1186/s12871-018-0568-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimal effective weight-based dosing of ondansetron to reduce hypotension in cesarean section under spinal anesthesia: a randomized controlled superiority trial

Abstract: BackgroundThe weight-based dosing of ondansetron to reduce hypotension has never been investigated. The aim of this study is to determine the optimal dose of ondansetron required based on the patient’s weight to reduce hypotension following spinal anesthesia for cesarean section.MethodsIn this prospective, triple-blinded, parallel group, randomized controlled trial, a total of 228 pregnant women were randomized to receive either normal saline (group NS) or ondansetron 0.05 mg/kg (group O1) or ondansetron 0.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Similarly, Ortiz et al 7 compared 2, 4, and 8 mg of ondansetron with a placebo and found that ondansetron had no pharmacological effect on reducing the incidence of spinal-induced hypotension or the amounts of vasopressor used in cesarean delivery. Oofuvong et al 8 tried to find the minimal effective dose of ondansetron that would prevent spinal-induced hypotension, but failed to observe this effect. It is difficult to explain the inconsistencies observed in these previously published reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ortiz et al 7 compared 2, 4, and 8 mg of ondansetron with a placebo and found that ondansetron had no pharmacological effect on reducing the incidence of spinal-induced hypotension or the amounts of vasopressor used in cesarean delivery. Oofuvong et al 8 tried to find the minimal effective dose of ondansetron that would prevent spinal-induced hypotension, but failed to observe this effect. It is difficult to explain the inconsistencies observed in these previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] However, there is some controversy surrounding this function of ondansetron. [6][7][8] Different research conditions used in different studies may contribute to this controversy, such as the dose of ondansetron that was used and the timing of administration. Studies have already suggested that 4 mg of ondansetron is more effective in this context compared to other doses.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotension is the most common problem associated with spinal anesthesia, and treatment for hypotension is more likely when this method is used 18,19 . The incidences of hypotension during spinal anaesthesia for cesarean section reported vary from 53 to 85% worldwide 20 . The possible mechanism of subarachnoid block-induced hypotension is related to spinal nerve sympathectomy, vasodilation of peripheral arteries, decreased venous reflux, and consequently decreased cardiac output 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Post-spinal anesthesia hypotension, which can occur as a result of combined spinal epidural (CSE) anesthesia during cesarean delivery, can lead to adverse maternal and fetal outcomes. [1][2][3][4] Therefore, effective prediction of maternal hypotension is of great clinical importance.…”
Section: Introductionmentioning
confidence: 99%